Application of polymerase chain reaction for rapid evaluation of hygienic status of milk - Deepa Mary.j.j (Department of Veterinary Public Health, College of Veterinary and Animal Sciences, 2008)
Rapid assessment of the bacterial load and detection of pathogens in milk is of public health significance. Molecular detection of pathogenic microorganisms is based on DNA amplification of the target pathogens. Therefore efficient extraction of DNA directly from milk is a major step. DNA could be efficiently extracted directly from milk by a prior sample preparation so as to remove the fat and milk proteins. The phenol chloroform method of DNA extraction was modified to reduce the time require for the procedure. The use of lysozyme helped the release of DNA from lysed gram positive Staphylococcus aureus. The extracted DNA was used as template in PCR. PCR was carried out with already published primers. PCR was modified with the use of PCR buffer containing PCR facilitators (BSA and Tween 20) to overcome PCR inhibition. The standardized procedure was used to assess the bacterial load and to detect Escherichia coli and S. aureus directly from milk. To assess the bacterial load dilutions of milk were made upto10-10. DNA was extracted from each dilution with which PCR was carried out with primers specific for Pseudomonas. Aerobic Plate Count was also done for the same samples and compared with PCR. It could be concluded that the approximate APC of the milk sample by PCR is next lower dilution to the dilution giving the PCR amplification. The total time taken for the analysis was approximately five hours. Extraction of DNA and PCR was done with primers for detection of E. coli from the same milk samples and compared with culture. Percentage of samples positive both by culture and PCR was 50 and negative by both methods were 30. Twenty percentage of the samples were positive by PCR and negative by culture. Extraction of DNA and PCR was done with primers for detection of S. aureus from the same milk samples and compared with culture. Percentage of samples positive both by culture and PCR was 60 and negative by both methods were 20. Twenty percentage of the samples were negative by PCR and positive by culture. Hence, protocol developed for detection of S. aureus needs further refinement to take care of false negative results by PCR, probably due to the low number of organisms present in milk.